Analysis of the Relationship Between Self-Confidence and Student Learning Activity in Science Learning Using YouTube-Based Problem-Based Learning - Khairunnisa, Sulis Janu Hartati, Sunardjo (Lembaga Bale Literasi, 2025)
Science education in schools still faces obstacles in the form of low self-confidence among students, which results in a lack of active participation during the learning process. Applying the Problem-Based studying (PBL) paradigm with YouTube video as a support, this research seeks to investigate the relationship between students' self-confidence and their degree of engagement in studying science. Students in eighth grade at a public junior high school were chosen at random to participate in the quantitative study, which used a correlational survey methodology. Two surveys, one measuring learning activity and the other self-confidence, were used. For data that was assumed to be regularly distributed, we used Pearson's correlation test; for data that did not, we used Spearman's test. A correlation coefficient of 0.713 and a significance value below 0.001 indicated a strong positive relationship between learning activities and self-confidence. According to the results, pupils are more engaged in their scientific education when they feel good about themselves. Finally, the PBL paradigm, which is based on YouTube, may be a useful alternative to traditional classroom instruction for boosting students' interest, engagement, and retention of scientific concepts.